Characterization and thermogravimetric analysis of oil shale from Uvurjargalant deposit - Bayasgalan, Khulan; Bayanmunkh, Myagmargerel; Baatar, Ulzii; Bayarkhuu, Bolormaa; Murneren, Tuya (Mongolian Journal of Chemistry, 2018)
The yield, properties and composition of soluble and insoluble (kerogen) of organic matter of oil shale from Uvurjargalant deposit of Mongolia have been investigated in this study. The study result shows that oil shale contains low amount of moisture and volatile products, while the ash yield is high (71.86 %) - which implies that most of the oil shale are minerals. The total amount of bitumens in the oil shale was very low (1.27 wt %), whereas kerogen content was 22.84 wt %, which is relatively high compared to oil shale from other deposits in Mongolia. Under IR spectral analysis and the ratio of hydrogen and carbon, the Uvurjargalant oil shale belongs to I type of oil shale. The thermogravimetric analysis showed that organic matter of oil shale decomposed at a temperature 300-750 ºC to produce gas and liquid products.